PENGARUH DUKUNGAN ORGANISASI, DUKUNGAN ATASAN, DAN DUKUNGAN REKAN KERJA YANG DIRASAKAN TERHADAP KINERJA PEGAWAI KAPANEWON GIRIMULYO KULON PROGO - Ahmad Jamil Hidayatullah; Ignatius Soni Kurniawan (Jurnal Ekonomi dan Bisnis (EK dan BI), 2023)
There is a phenomenon that occurs at the Kapanewon Girimulyo Kulon Progo Office, where performance achievements are not yet optimal. This is because there is a workforce that is not yet able to face every challenge and change in dealing with every challenge around them, including in the use of information technology to support community services. This research aims to analyze the influence of organizational support, superior support, and co-worker support on the performance of Kapanewon Girimulyo Kulon Progo Yogyakarta employees. This research is quantitative research that uses primary data collection with a research instrument in the form of a questionnaire. There were 21 research participants, and the data was taken by census. The data was processed using multiple regression analysis using the SPSS software application. The research results found that organizational support, supervisory support, and work support had a significant positive effect on employee performance. This research proves that strengthening antecedents has implications for organizations when organizations make policies and decisions to improve employee performance. The number of employees who were respondents was only small, which was a limitation in this research.